PENGARUH KUALITAS LAYANAN ELEKTRONIK ULASAN ELEKTRONIK PROMOSI TERHADAP KEPERCAYAAN PELANGGAN DAN KEPUTUSAN PEMBELIAN LAYANAN PENGANTARAN MAKANAN ONLINE DI SAMARINDA - Hadi, Amirul; Ilman, Rizqin; Putra Nugraha, Noviandy; Azhari, Fachmi; Haryanto, Iwan; Firlianzo, Muhammad; Rahmawati, Rahmawati (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the effect of E-Service Quality, Electronic Word of Mouth (eWOM), and Promotion on Customer Trust and Purchase Decisions in online food delivery services (GoFood, GrabFood, ShopeeFood) in Samarinda. The growth of the digital economy requires a deep understanding of the factors that drive consumer decisions. This study uses a quantitative approach with a survey method of application users in Samarinda City. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that E-Service Quality, eWOM, and Promotion had a positive and significant effect on Customer Trust. In addition, the three independent variables, along with Customer Trust as a mediating variable, have a positive effect on Purchase Decisions. These findings indicate that to win the market in Samarinda, service providers must optimize application interfaces, manage customer reviews, and design strategic promotions to build trust that leads to purchases.